Status of adoption of improved fish production technology in Rupandehi, Nepal - Neupane, Sudip; Gharti, Kamala (International Journal of Applied Sciences and Biotechnology, 2018)
Aquaculture plays an important role to increase farm income and hence alleviate widespread poverty in the country. Fish is considered as the principal source of animal protein. The research was conducted to assess the status of adoption of improved fish production technologies available in the Rupandehi, Nepal. The research was designed to ascertain the socio-demographic characteristics of the farmers, determine available technologies on fish production, determine awareness and adoption of the available technologies and identify the major problems faced by farmers in using improved fish production technologies. Purposive sampling procedure was used to select 100 respondents for the study. Data were analyzed using frequency count, percentages, standard deviation and indexing. The result shows that average age of the respondents was 39.8 years. Eighty percent respondents had post-secondary school certificate. Major sources of information of fish farming were trainings and information and communication technologies. Average pond size of respondents was 0.8 ha. Most of the respondents were aware of the technologies and adopted them. Indexing showed that High cost of fish feed was ranked as the major problem followed by high cost of fingerlings and inadequate capital in using improved fish production technology.